The Impact of Crisis Management Strategy on the Performance of the Employees of Arab Potash Company "an Applied Study" (International Journal of Scientific Research and Management (IJSRM), 2018)
The study aimed at recognizing the crisis management strategy and its impact on in the performance of employees of Arab Potash company . The problem with the study is that the Arab Potash Company is under internal and external pressure can lead to a real crisis affecting the performance of employees and the resulting disruption of production and lower profits. To achieve the aim of the study self administrated questionnaire was used to collect the data . it was developed and disrributed to asample of (248) individuals. However, 8 copies were excluded for not being suitable for statistical analysis, so that the number of questionable questionnaires eligible for statistical analysis equal (240) copies. This data has been analyzed using SPSS 16. The study concluded many conclusions from them, potash company management teams used to work as a management methods to solve the problems they face, draw upon the company’s management strategy change course when faced by crises is clear-cut, with the company’s management is convinced that the tactical reserve strategy necessary to respond to crises. The study many of the recommendations, including, the need for concerted government and private efforts to reach appropriate solutions to mitigate the crises facing the Jordanian companies, the need to provide a center for the preparation of leaders and managers of companies, and equip them with the necessary capacity to deal with crises. The study suggested a more specialized in the field of crisis management studies.